Law, Silence, and Digital Recourse: Addressing Bullying and Body Shaming in Indonesian Higher Education - Marzuki, Ismail; Moh. Zainuddin Sunarto (Jurnal Cakrawala Hukum, 2025)
Bullying and body shaming in Indonesian higher education persist not because the law is absent, but because it remains systematically inaccessible to those who suffer its violations. Existing legal instruments including Articles 310, 315, and 351 of the Criminal Code, Article 27A of the ITE Law, and Ministerial Regulation No. 55 of 2024 provide a formally adequate normative framework, yet their enforcement is consistently undermined by institutional silence, hierarchical campus culture, and the absence of trusted reporting mechanisms. This study examines the effectiveness of that legal framework and evaluates the capacity of an electronic complaint system to function as a legally grounded instrument for institutional response to bullying and body shaming in the campus environment. Employing a socio-legal research design that integrates direct observation, in-depth interviews, focus group discussions, and systematic legal analysis, the study was conducted at the Faculty of Social Sciences and Humanities, Universitas Nurul Jadid, in August 2024. The findings demonstrate that the e-complaint system measurably reduces the structural barriers to victim reporting by providing anonymity, real-time complaint tracking, and digitally admissible evidentiary records. However, its full legal potential is contingent upon compliance with the Personal Data Protection Law, institutional embedding within Regulation No. 55/2024's Satgas framework, and sustained commitment to anti-retaliation enforcement. Law and technology, this study concludes, are most effective not as alternatives but as mutually reinforcing instruments of institutional accountability.